Chemical mechanical polishing composition for metal alloy and polishing method thereof
By adding nanoclay and organic phosphonic acid to the chemical mechanical polishing composition, the problems of high surface roughness, many defects, short recirculation time and high corrosion risk during the surface polishing process of metal alloy substrates in the prior art are solved, and high efficiency and low defect polishing effect and long recirculation time are achieved.
Patent Information
- Application Number
- CN202380059717.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-03
- Filing Date
- 2023-12-06
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-12-06
AI Technical Summary
In the polishing process of metal alloy substrates, the existing chemical mechanical polishing compositions have problems such as high surface roughness, many defects, short recirculation time and high corrosion risk.
A chemical mechanical polishing composition comprising alumina abrasive particles, an oxidant, a complexing agent, a dispersant and a pH adjuster is used, wherein the dispersant is nanoclay, which has a z-average particle size of up to 1000 nm, and organic phosphonic acid is added to the composition as the complexing agent to achieve high material removal rate, low surface defect number and long recirculation time.
High material removal rate, low surface roughness, low surface defect number and long recycling time on the surface of the metal alloy substrate are achieved, while avoiding the corrosion risk of acidic compositions on the polishing equipment.
Smart Images

Figure BDA0005271119730000191 
Figure BDA0005271119730000201 
Figure BDA0005271119730000221
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical engineering, and in particular relates to a chemical mechanical polishing composition for metal alloys and a polishing method. Background Art
[0002] Chemical Mechanical Polishing (CMP) is a common process for achieving global planarization in integrated circuit manufacturing or other fields. This process is mainly used to obtain a smooth surface that is flat and free of scratches and impurities. This process polishes various target substrates through a combination of chemical and mechanical forces, and chemical mechanical polishing (CMP) compositions play a decisive role in this process. These compositions are usually aqueous solutions containing various chemical additives and abrasives that are evenly dispersed. CMP compositions are also called polishing slurries, polishing liquids, or polishing compositions, etc., and are commonly used to polish the surfaces of various substrates (such as metals, metal alloys, minerals, and plastics).
[0003] There is a widespread demand for polishing metal substrates and metal alloy substrates, such as vehicles, ships, aircraft, pipelines, light reflectors, containers, handrails, kitchen utensils, cooking utensils, architectural metals and jewelry. Most of the metal parts need to be polished. Among them, ferroalloy substrates (such as stainless steel with good corrosion resistance) are widely used in machine tools, cooking utensils, structural materials such as surgical knives, transportation equipment, consumer electronic equipment parts such as smartphone parts, laptop computer shells, metal crafts such as car trademarks, etc., so there is also a demand for polishing the stainless steel surface.
[0004] CMP compositions containing aluminum oxide abrasives are usually used to polish materials containing iron alloys to obtain substrates with smooth mirror surfaces. Many applications of metal alloys require low surface roughness, high brightness and smooth mirror effects, which can be achieved by CMP compositions containing aluminum oxide abrasives. However, aluminum oxide abrasives can easily cause pits, scratches and other surface defects on the surface of metal alloy substrates. Due to lack of oxygen and local destruction of the protective passivation film of stainless steel, such surface defects can cause corrosion problems in ferrous metal alloys such as stainless steel. And in daily use, these surface defect sites are easily contaminated by dirt and bacteria. Therefore, there is still a need for a CMP composition containing aluminum oxide abrasives suitable for surface polishing of metal alloy substrates that can achieve low surface roughness and low number of surface defects.
[0005] In order to reduce manufacturing costs, reduce waste and reduce environmental burden, CMP compositions are usually recycled during the polishing process of metal alloy substrates. For example, the CMP composition is used for polishing, then discharged from the polishing device and collected in a tank, and then recycled back to the polishing device for further polishing. Therefore, it is necessary to enable the CMP composition containing aluminum oxide abrasives to have a long recycling time. The recycling time refers to the time during which the composition can be used again for chemical mechanical polishing of the substrate without an overall decrease in polishing performance (such as material removal rate). However, when recycled, the activity of the CMP composition often decreases over time, which may be due to wear, cracking and shrinkage of the aluminum oxide particles during the polishing process, or due to chemical changes in the aluminum oxide particles. The reduction in the polishing activity of the CMP composition leads to a reduction in the time that the CMP composition can be recycled for polishing, and replacing the CMP composition will lead to an increase in manufacturing costs and environmental burden. At the same time, the chemical mechanical polishing compositions currently on the market for polishing stainless steel are generally acidic, and there is a risk of corroding iron and stainless steel parts in chemical mechanical polishing equipment. Therefore, there is still a need for a CMP composition containing aluminum oxide abrasives suitable for polishing the surface of a metal alloy substrate that can achieve higher removal rates, longer recycling times, and low surface defect counts and has a neutral pH value. Summary of the invention
[0006] One object of the present invention is to overcome the above-mentioned problems existing in the prior art. Specifically, the embodiments of the present invention provide a composition suitable for chemical mechanical polishing of a metal alloy substrate surface, which, on the one hand, exhibits a high material removal rate and a longer recycle time, and on the other hand, can achieve low surface roughness and low number of surface defects, and has a neutral pH value, without the risk of corroding metal parts in the polishing equipment.
[0007] Specifically, the chemical mechanical polishing composition of the present invention comprises aluminum oxide abrasive grains, an oxidizing agent, a complexing agent, a dispersant, and a pH adjuster, wherein the dispersant is nanoclay having a z-average particle size of at most 1000 nm.
[0008] Preferably, the nanoclay has a Zeta potential value of at least -5 mV.
[0009] Preferably, the aluminum oxide abrasive grains have a negative zeta potential at a pH of 6 to 7 in the composition.
[0010] Preferably, the oxidant is an inorganic peroxide, an organic peroxide, or a combination thereof.
[0011] Preferably, the composition further comprises a complexing agent, and the complexing agent is a dicarboxylic acid, a polycarboxylic acid, an amino acid, an organic amine, an aminocarboxylic acid, a polyaminopolycarboxylic acid, a phosphate, a polyphosphate, an organic phosphonic acid, a phosphonocarboxylic acid, a phenol derivative, a ketone, and a combination thereof.
[0012] Preferably, the complexing agent is an organic phosphonic acid.
[0013] Preferably, the composition comprises 0.1 wt% to 33.3 wt% of a complexing agent.
[0014] Preferably, the composition comprises 0.0001 wt% to 15 wt% nanoclay.
[0015] Preferably, the pH adjuster is an alkali metal hydroxide, a quaternary ammonium hydroxide, an alkali metal carbonate, or a combination thereof.
[0016] Another object of an embodiment of the present invention is to provide a polishing method for a metal alloy substrate, wherein the method is implemented using the above composition.
[0017] The CMP composition provided by the present invention can not only achieve a high material removal rate in the chemical mechanical polishing of a metal alloy substrate, but also has a neutral pH value, no risk of metal equipment corrosion, and can achieve a longer recycling time, is environmentally friendly, and has higher economic benefits. The product polished with the CMP composition of the present invention has low surface roughness, low number of surface defects (scratches and pits) and a satisfactory mirror effect. DETAILED DESCRIPTION
[0018] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] The chemical mechanical polishing composition generally comprises abrasive particles dispersed in an aqueous carrier. The abrasive particles can help remove material from the surface of the substrate during polishing. Preferably, the abrasive particles can be metal oxide abrasive particles selected from cerium oxide (ceria), aluminum oxide (aluminum oxide), silicon oxide (silicon dioxide), zirconium oxide (zirconium oxide), titanium oxide (titania), germanium oxide (germanium oxide), magnesium oxide (magnesium oxide), nickel oxide, gallium oxide (gallium oxide), yttrium oxide (yttrium oxide), and combinations thereof. Preferably, the abrasive particles contain at least 67 wt% (weight percentage), more preferably at least 74 wt%, more preferably at least 81 wt%, more preferably at least 88 wt%, and most preferably at least 93 wt% aluminum oxide. In a particularly preferred embodiment, the abrasive particles are all aluminum oxide abrasive particles.
[0020] When used, the composition preferably contains at least 0.02wt%, more preferably at least 0.24wt%, more preferably at least 0.63wt%, more preferably at least 0.82wt%, and most preferably at least 1.0wt% of abrasive particles. The term "when used" as used herein refers to the moment when the composition is applied to the surface of the substrate during chemical mechanical polishing. If the concentration of abrasive particles is too high, the composition may cause undesirable surface defects such as substrate scratches during polishing. Therefore, when used, the composition preferably contains at most 40wt%, more preferably at most 35wt%, more preferably at most 30wt%, more preferably at most 25wt%, and most preferably at most 20wt% of abrasive particles. In a preferred embodiment, the composition contains 0.02wt% to 40wt%, more preferably 0.24wt% to 35wt%, more preferably 0.63wt% to 30wt%, more preferably 0.63wt% to 25wt%, and most preferably 1.0wt% to 20wt% of abrasive particles.
[0021] As known to those skilled in the art, the aluminum oxide abrasive grains may be fumed aluminum oxide or aluminum oxide with different crystal phases, such as α-aluminum oxide, β-aluminum oxide, γ-aluminum oxide, δ-aluminum oxide, θ-aluminum oxide, σ-aluminum oxide, κ-aluminum oxide, η-aluminum oxide, χ-aluminum oxide, p-aluminum oxide, and combinations thereof. Preferably, the aluminum oxide abrasive grains are selected from α-aluminum oxide, β-aluminum oxide, γ-aluminum oxide, δ-aluminum oxide, σ-aluminum oxide, θ-aluminum oxide, and combinations thereof.
[0022] It has been demonstrated that α-alumina can exhibit a higher substrate material removal rate during chemical mechanical polishing compared to alumina abrasive grains having other crystalline phases. Therefore, the alumina abrasive grains preferably contain at least 6 wt%, more preferably at least 11 wt% of α-alumina. As known to those skilled in the art, the amount of α-alumina can be obtained by X-ray diffraction (XRD), for example, using a D8 X-ray diffractometer (Bruker Corp) based on the integrated intensity ratio of the (113) plane. However, a large amount of α-alumina can lead to an increase in the number of defects such as scratches and pits on the substrate surface. The inventors have found that the composition of the present invention can exhibit a high material removal rate even when the α-alumina content is low, thereby generating a smaller number of defects on the substrate surface. Therefore, preferably, the alumina abrasive grains contain up to 96 wt%, more preferably up to 95 wt% of α-alumina. In a preferred embodiment, the alumina abrasive grains contain 6 wt% to 96 wt%, more preferably 11 wt% to 95 wt% of α-alumina.
[0023] Preferably, the aluminum oxide abrasive grains contain a mixture of α-aluminum oxide and aluminum oxide having a non-α crystalline phase. The aluminum oxide having a non-α crystalline phase may be any aluminum oxide except α-aluminum oxide, such as β-aluminum oxide, γ-aluminum oxide, δ-aluminum oxide, θ-aluminum oxide, σ-aluminum oxide, κ-aluminum oxide, η-aluminum oxide, χ-aluminum oxide and p-aluminum oxide, or a combination thereof. Preferably, the aluminum oxide having a non-α crystalline phase is selected from β-aluminum oxide, γ-aluminum oxide, δ-aluminum oxide, σ-aluminum oxide, θ-aluminum oxide, and a combination thereof. Preferably, the aluminum oxide abrasive grains contain at least two crystalline phases, more preferably at least three crystalline phases. The inventors have found that the aluminum oxide abrasive grains as described herein can reduce the number of surface defects of the substrate and can reduce the surface roughness of the substrate surface, thereby helping to improve the visual effect of mirror finishing to obtain a bright and reflective surface.
[0024] The average particle size (diameter) of the abrasive particles will affect the material removal rate. As known to those skilled in the art, the average particle size of the abrasive particles can be obtained by measuring the composition by laser diffraction (for example, using LA-960 from Horiba). The curve obtained by this measurement provides the cumulative volume percentage of particles of a certain size, from which the corresponding D10, D30, D50, D70 and D90 values can be obtained. The particle size of the aluminum oxide abrasive particles mentioned here is obtained by the particle size distribution of the aluminum oxide abrasive particles measured in the composition.
[0025] The average particle size (D50) of the aluminum oxide abrasive corresponds to a value where 50% by volume of the particles have a particle size less than this value. A smaller D50 will result in a lower material removal rate. Preferably, the abrasive has a D50 of at least 0.09 μm, more preferably at least 0.41 μm, more preferably at least 1.28 μm, more preferably at least 1.72 μm, and most preferably at least 2.01 μm as measured by laser diffraction. However, if the D50 of the aluminum oxide abrasive is too large, a large number of undesirable surface defects, such as scratches and pits, will appear during the CMP process. Therefore, the abrasive preferably has a D50 of at most 15 μm, more preferably at most 12 μm, more preferably at most 10 μm, more preferably at most 8 μm, and most preferably at most 6 μm as measured by laser diffraction. In a preferred embodiment, the abrasive particles have a D50 measured by laser diffraction of 0.09 μm to 15 μm, more preferably 0.41 μm to 12 μm, more preferably 1.28 μm to 10 μm, more preferably 1.72 μm to 8 μm, more preferably 2.01 μm to 6 μm.
[0026] The numerical value corresponding to D10 is: 10% by volume of the particles have a particle size smaller than this value. Experiments have shown that a smaller D10 can achieve a smaller surface roughness during the CMP process. The D10 of the aluminum oxide abrasive mentioned here is obtained by the particle size distribution of the aluminum oxide abrasive measured in the composition. Preferably, the abrasive has a D10 measured by laser diffraction of at most 10 μm, more preferably at most 8 μm, more preferably at most 6 μm, more preferably at most 4 μm, and most preferably at most 3 μm. However, a smaller D10 of aluminum oxide abrasives will reduce the material removal rate. Preferably, the abrasive has a D10 measured by laser diffraction of at least 0.005 μm, more preferably at least 0.009 μm, more preferably at least 0.02 μm, more preferably at least 0.04 μm, and most preferably at least 0.08 μm. In a preferred embodiment, the abrasive particles have a D10 measured by laser diffraction of 0.005 μm to 10 μm, more preferably 0.009 μm to 8 μm, more preferably 0.02 μm to 6 μm, more preferably 0.04 μm to 4 μm, most preferably 0.08 μm to 3 μm.
[0027] The numerical value corresponding to D30 is: 30% by volume of the particles have a particle size smaller than this value. Experiments have shown that a smaller D30 of aluminum oxide abrasives can achieve a smaller surface roughness during CMP treatment. The D30 of the aluminum oxide abrasives mentioned here is obtained from the particle size distribution of the aluminum oxide abrasives measured in the composition. Preferably, the abrasive has a D30 measured by laser diffraction of at most 12.5 μm, more preferably at most 11 μm, more preferably at most 9 μm, more preferably 7 μm, and most preferably at most 5 μm. However, a smaller D30 of aluminum oxide abrasives will reduce the material removal rate. Preferably, the abrasive has a D30 measured by laser diffraction of at least 0.009 μm, more preferably at least 0.02 μm, more preferably at least 0.05 μm, more preferably at least 0.81 μm, and most preferably at least 1.12 μm. In a preferred embodiment, the abrasive particles preferably have a D30 measured by laser diffraction of 0.009 μm to 12.5 μm, more preferably 0.02 μm to 11 μm, more preferably 0.05 μm to 9 μm, more preferably 0.81 μm to 7 μm, most preferably 1.12 μm to 5 μm.
[0028] D70 corresponds to a numerical value: 70% by volume of the particles have a particle size smaller than this value. A higher D70 of the aluminum oxide abrasive results in a higher material removal rate. The D70 of the aluminum oxide abrasive mentioned here is obtained from the particle size distribution of the aluminum oxide abrasive measured in the composition. Preferably, the abrasive has a D70 measured by laser diffraction of at least 0.13 μm, more preferably at least 0.34 μm, more preferably at least 0.78 μm, more preferably at least 1.71 μm, and most preferably at least 2.68 μm. However, if the D70 of the aluminum oxide abrasive is too large, a large number of unfavorable surface defects such as scratches and pits will appear during the CMP process. Preferably, the abrasive has a D70 measured by laser diffraction of at most 19 μm, more preferably at most 16 μm, more preferably at most 13 μm, more preferably at most 10 μm, and most preferably at most 8 μm. In a preferred embodiment, the abrasive particles preferably have a D70 measured by laser diffraction of 0.13 μm to 19 μm, more preferably 0.34 μm to 16 μm, more preferably 0.78 μm to 13 μm, more preferably 1.71 μm to 10 μm, most preferably 2.68 μm to 8 μm.
[0029] D90 corresponds to a numerical value: 90% by volume of the particles have a particle size smaller than this value. A higher D90 of the abrasive grains results in a higher material removal rate. The D90 of the aluminum oxide abrasive grains mentioned here is obtained from the particle size distribution of the aluminum oxide abrasive grains measured in the composition. Preferably, the abrasive grains have a D90 measured by laser diffraction of at least 0.16 μm, more preferably at least 1.58 μm, more preferably at least 2.15 μm, more preferably at least 3.26 μm, and most preferably at least 4.42 μm. However, if the D90 is too large, a large number of unfavorable surface defects such as scratches and pits will appear during the CMP process. Preferably, the abrasive grains have a D90 measured by laser diffraction of at most 25 μm, more preferably at most 21 μm, more preferably at most 18 μm, more preferably at most 15 μm, and most preferably at most 12 μm. In a preferred embodiment, the abrasive particles have a D90 measured by laser diffraction of 0.16 μm to 25 μm, more preferably 1.58 μm to 21 μm, more preferably 2.15 μm to 18 μm, more preferably 3.26 μm to 15 μm, most preferably 4.42 μm to 12 μm.
[0030] The abrasive particles should have a suitable BET surface area. The BET surface area can be measured by a person skilled in the art using the Brunauer-Emmett-Teller method by adsorbing nitrogen on the abrasive particle surface. A larger surface area of the particle can increase the contact area between the particle and the substrate, thereby improving the material removal rate. Therefore, the abrasive particles preferably have a surface area of at least 2.1 m 2 / g, more preferably at least 6.4m 2 / g, more preferably at least 10.1m 2 / g, most preferably at least 16.3m2 The abrasive particles preferably have a BET surface area of at most 94.7 m 2 / g, more preferably up to 81.2m 2 / g, more preferably up to 72.9m 2 / g, most preferably up to 60.6m 2 / g of BET surface area.
[0031] Preferably, the abrasive particles have a positive charge. Charge refers to the zeta potential, which can be measured, for example, by a Mastersizer S (Malvern Instruments). As known to those skilled in the art, the zeta potential of the abrasive particles in the composition refers to the potential at the interface between the mobile fluid in the composition and the fluid stabilizing layer attached to the abrasive particles dispersed in the composition. A higher zeta potential results in a stronger electrostatic repulsion between the particles, thereby increasing the stability of the dispersion of the particles in the composition. Preferably, the abrasive particles have a negative zeta potential in the composition at a pH of 6 to 7, preferably, the abrasive particles have a zeta potential of at least -0.5 mV, more preferably at least -1 mV, more preferably at least -2 mV, most preferably at least -3 mV in the composition at a pH of 6 to 7. Preferably, the abrasive particles have a zeta potential of up to -50 mV, more preferably at most -40 mV, more preferably at most -30 mV, most preferably at most -20 mV in the composition at a pH of 6 to 7. Preferably, the abrasive particles have a zeta potential of -0.5 mv to -50 mV, more preferably -1 mV to -40 mV, more preferably -2 mV to -30 mV, more preferably -3 mV to -20 mV at a pH of 6 to 7 in the composition.
[0032] The composition further comprises an oxidant. Depending on the substrate, the oxidant can react with the substrate surface and promote the material removal of the substrate during the polishing process. The oxidant can specifically be an inorganic percompound, an organic percompound, or a combination thereof, such as hydrogen peroxide, percarbonate, benzyl peroxide, peracetic acid, dibutyl peroxide, monopersulfate, dipersulfate, peroxide, urea peroxide, perchlorate, periodate, perborate, perbromate, permanganate, or a combination thereof.
[0033] Preferably, the oxidizing agent is an inorganic peroxide. The oxidizing agent may be present in the composition in any suitable form, such as an acid, a conjugate acid, a salt (e.g., a potassium salt, a sodium salt, an ammonium salt) or a combination thereof. The oxidizing agent according to the present invention may improve the material removal rate of the substrate during the polishing process.
[0034] Too low a concentration of the oxidizing agent will reduce the material removal rate of the substrate during the polishing process. Preferably, when used, the composition comprises at least 0.01 wt%, more preferably at least 0.06 wt%, more preferably at least 0.12 wt%, more preferably at least 0.28 wt%, most preferably at least 0.51 wt% of the oxidizing agent. Preferably, when used, the composition comprises at most 15 wt%, more preferably at most 10 wt%, more preferably at most 8 wt%, more preferably at most 7 wt%, most preferably at most 6 wt% of the oxidizing agent. In a preferred embodiment, when used, the composition comprises 0.01 wt% to 15 wt%, more preferably 0.06 wt% to 10 wt%, more preferably 0.12 wt% to 8 wt%, more preferably 0.28 wt% to 7 wt%, most preferably 0.51 wt% to 6 wt% of the oxidizing agent.
[0035] The composition further comprises a complexing agent. The complexing agent can bind metal ions that may be formed during the chemical mechanical polishing process. Depending on the substrate being polished, the complexing agent can increase the material removal rate during the polishing process. Suitable complexing agents are dicarboxylic acids, polycarboxylic acids, amino acids, organic amines, aminocarboxylic acids, polyaminopolycarboxylic acids, phosphates, polyphosphates, organic phosphonic acids, phosphonocarboxylic acids, phenol derivatives, ketones, or combinations thereof. The complexing agent can be present in the composition in any suitable form, such as an acid, a conjugate acid, a salt (e.g., a potassium salt, a sodium salt, an ammonium salt), or a combination thereof. .
[0036] Examples of dicarboxylic acids include oxalic acid, malonic acid, succinic acid, maleic acid, phthalic acid, tartaric acid, aspartic acid, glutamic acid, gluconic acid, and combinations thereof. Examples of polycarboxylic acids include citric acid, butanetetracarboxylic acid, and combinations thereof. Examples of organic amines include ethylenediamine, diethylenetriamine, trimethyltetramine, and combinations thereof. Examples of aminopolycarboxylic acids include ethylenediaminetetraacetic acid (EDTA), hydroxyethylethylenediaminetriacetic acid (HEDTA), triethylene glycol diaminetetraacetic acid (EGTA), diethylenetriaminepentaacetic acid (DTPA), diaminohydroxypropanetetraacetic acid (DTPA-OH), triethylenetetraaminehexaacetic acid (TTHA), iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), bisaminophenoxyethanetetraacetic acid (BAPTA), tetraxetan (DOTA), nicotinamide, ethylenediaminebishydroxyphenylacetic acid (EDDHA), nitrilotriacetic acid, and combinations thereof. Examples of organic phosphonic acids are ethylenediaminetetrakis(methylenephosphonic acid) (EDTMP), aminotris(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid) (DTPMP), 2-aminoethylphosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP), 6-hexyldiphosphonic acid, 1,5-pentenediphosphonic acid, 1,4-phenyldiphosphonic acid, xylenediphosphonic acid, diethylenetriaminepenta(methylenephosphonic acid), hexamethylenediamine-N,N,N',N'-tetrakis(methylphosphonic acid), bis(hexamethylenetriaminepenta(methylenephosphonic acid)), aminotris(methylenephosphonic acid)), methylphosphonic acid, (aminomethyl)phosphonic acid, nitrotrimethylenephosphonic acid, 4-amino-1- Hydroxybutane-1,1-diphosphonic acid, iminobis(methylphosphonic acid), (1-hydroxy-2-(1H-imidazol-1-yl)ethane-1,1-diyl)diphosphonic acid, ethylenediaminetetra(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, methanehydroxyphosphonic acid, 1-phosphonobutane-2,3,4-tricarboxylic acid, nitrilotriacetic acid, sodium nitrilotriacetate, ammonium nitrilotriacetate, aminotri(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1-hydroxy-1,1,2-triphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, α-methylphosphonic acid, and combinations thereof. Examples of ketones include 1,3-diketone and the like.
[0037] Preferably, the complexing agent is an organic phosphonic acid. The organic phosphonic acid may have one, two, three or more phosphonic acid groups. Preferably, the complexing agent is an organic diphosphonic acid. In the most preferred embodiment, the complexing agent is HEDP, which is an organic diphosphonic acid that can complex iron, copper, zinc, has good corrosion and scale inhibition properties, and has good chemical stability at high pH values. It has been found that the complexing agent of the present invention increases the material removal rate of the substrate during CMP processing.
[0038] Preferably, when used, the composition comprises at least 0.1 wt%, more preferably at least 0.5 wt%, more preferably at least 1.1 wt%, more preferably at least 2.2 wt%, most preferably at least 5.2 wt% of a complexing agent. Preferably, when used, the composition comprises at most 33.3 wt%, more preferably at most 27.5 wt%, more preferably at most 19.8 wt%, more preferably at most 15.2 wt%, most preferably at most 10.1 wt% of a complexing agent. In a preferred embodiment, the composition comprises 0.1 wt% to 33.3 wt%, more preferably 0.5 wt% to 27.5 wt%, more preferably 1.1 wt% to 19.8 wt%, more preferably 2.2 wt% to 15.2 wt%, more preferably 5.2 wt% to 10.1 wt% of a complexing agent.
[0039] The composition comprises an aqueous carrier. The abrasive and chemical additives are suspended in the aqueous carrier. The aqueous carrier enables the abrasive and chemical additives to contact the substrate and the polishing pad during the CMP process. The aqueous carrier can be any component suitable for suspending the abrasive and the oxidant. Examples of the aqueous carrier are water, ethers (such as dioxane and tetrahydrofuran), alcohols (such as methanol and ethanol), and combinations thereof. Preferably, the aqueous carrier contains at least 50 wt%, more preferably at least 70 wt%, more preferably at least 90 wt%, more preferably at least 95 wt%, and most preferably at least 99 wt% of water. Preferably, the water is deionized water.
[0040] The composition comprises a pH adjusting agent when used. The pH adjusting agent helps the composition achieve a suitable pH. The pH adjusting agent can be a base or a salt thereof. The base or a salt thereof can be an organic base, an inorganic base, or a combination thereof.
[0041] Examples of inorganic bases include alkali metal hydroxides (e.g., potassium hydroxide, sodium hydroxide, lithium hydroxide), alkaline earth metal hydroxides (e.g., magnesium hydroxide, calcium hydroxide, beryllium hydroxide), alkali metal carbonates (e.g., potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, lithium bicarbonate), alkaline earth metal carbonates (e.g., magnesium carbonate, calcium carbonate, beryllium carbonate), alkali metal phosphates (e.g., tripotassium phosphate, trisodium phosphate, dipotassium phosphate, disodium phosphate), alkaline earth metal phosphates (e.g., magnesium phosphate, calcium phosphate, beryllium phosphate), ammonium carbonate, ammonium bicarbonate, ammonium hydroxide, and combinations thereof.
[0042] Examples of organic bases are aliphatic amines, aromatic amines, quaternary ammonium hydroxides (eg, tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH)), and combinations thereof.
[0043] Preferably, the pH adjusting agent is an alkali metal hydroxide, a quaternary ammonium hydroxide, an alkali metal carbonate, or a combination thereof. In a particularly preferred embodiment, the pH adjusting agent is selected from tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, potassium hydroxide, sodium hydroxide, potassium carbonate, potassium bicarbonate, sodium carbonate, sodium bicarbonate, and combinations thereof. It has been found that the pH adjusting agent of the present invention can increase the material removal rate of the substrate during CMP treatment. The composition may include a pH adjusting agent at a concentration suitable for achieving the pH of the present invention.
[0044] The composition may also optionally include a pH buffer. The pH buffer helps maintain a suitable pH for the composition. The pH buffer may be any suitable buffer. The pH buffer may be, for example, a phosphate, sulfate, acetate, borate, ammonium salt, or a combination thereof. The composition may include a pH buffer at a concentration suitable for maintaining the pH of the present invention.
[0045] The pH of the composition affects the removal rate of the substrate during the CMP process. It has been found that alkaline pH leads to lower material removal rates, while acidic pH brings the risk of corrosion of iron and stainless steel parts in chemical mechanical polishing equipment, so preferably, when used, the composition has a pH of at least 4.5, more preferably at least 5.0, more preferably at least 5.5, and most preferably at least 6.0. Preferably, when used, the composition has a pH of at most 8.5, more preferably at most 8.0, more preferably at most 7.5, and most preferably at most 7.0. In a preferred embodiment, when used, the pH range of the combination is 4.5 to 8.5, more preferably 5.0 to 8.0, more preferably 5.5 to 7.5, and most preferably 6.0 to 7.0.
[0046] The composition further comprises a dispersant, which helps to disperse the aluminum oxide abrasive grains and keep them stable in the solution, thereby improving the shelf life. The dispersant is preferably nanoclay, polyacrylic acid, sodium dodecylbenzene sulfonate, tetrasodium pyrophosphate, sodium hexametaphosphate, or a combination thereof. In a particularly preferred embodiment, the dispersant is nanoclay. Wherein, the term "nanoclay" as used herein refers to clay whose z-average particle size is at most 1000nm. The nanoclay can be any type of nanoclay, such as natural clay, synthetic clay, modified clay, or a combination thereof. Examples of nanoclays include kaolin (e.g., kaolin, dickite, halloysite, nacrite), montmorillonite (e.g., saponite, hectorite, laponite, nontronite, beidellite, magnesite, bentonite, andalusite, kyanite, sillimanite, kaolinite, metakaolin, mullite, aluminum silicate, aluminum dihydrate silicate, potassium aluminum silicate, sodium aluminum silicate, calcium aluminum silicate, aluminum silicate, magnesium aluminum silicate, boroaluminum silicate), illite (e.g., micas such as phlogopite, biotite, ferrolithium mica, muscovite, glauconite), chlorite, palygorskite, sepiolite, vermiculite, talc, pyrophyllite, modifications of such nanoclays, and combinations thereof. In a preferred embodiment, the nanoclay is montmorillonite. In a particularly preferred embodiment, the nanoclay is selected from bentonite, laponite, magnesium aluminum silicate, kaolinite, or a combination thereof.
[0047] For example, the nanoclay can be purchased from Shengxinxin Chemical Technology Co., Ltd. (Guangzhou, China).
[0048] It was found that the composition comprising nanoclay of the present invention can extend the shelf life of the composition, and it was also found that the nanoclay of the present invention can reduce the decrease in material removal rate during recycling.
[0049] Preferably, when used for polishing, the composition comprises at least 0.0001wt%, more preferably at least 0.001wt%, more preferably at least 0.01wt%, more preferably at least 0.03wt%, most preferably at least 0.05wt% of nanoclay. However, the amount of nanoclay should not be too high because it will hinder the interaction between the abrasive and the substrate surface, thereby reducing the material removal rate during the CMP process. Therefore, when used, the composition preferably comprises at most 15wt%, more preferably at most 13wt%, more preferably at most 12wt%, more preferably at most 11wt%, most preferably at most 10wt% of nanoclay. In a preferred embodiment, the composition comprises 0.0001wt% to 15wt%, more preferably 0.001 to 13wt%, more preferably 0.01wt% to 12wt%, more preferably 0.03wt% to 11wt%, more preferably 0.05wt% to 10wt% of nanoclay.
[0050] The composition should have a high viscosity. The viscosity can be measured in mPa*s (milliPascal seconds) at 25°C using a NDJ-8S viscometer (Shanghai Lichen Instrument Technology Co., Ltd.). The high viscosity of the composition can be achieved, for example, by the nanoclay of the present invention. It was found that the viscosity of the present invention can reduce the aggregation and agglomeration of abrasive particles and achieve fewer defects on the surface of the substrate. Preferably, the composition has a viscosity of at least 2 mPa*s, more preferably at least 5 mPa*s, and most preferably at least 8 mPa*s when measured as a 2% solution at 25°C; preferably, the composition has a viscosity of at most 903 mPa*s, more preferably at most 80 mPa*s, and most preferably at most 70 mPa*s when measured as a 2% solution at 25°C.
[0051] Preferably, the nanoclay is negatively charged. The greater the absolute value of the negative Zeta potential of the nanoclay, the more stable the dispersion system. Preferably, the value of the Zeta potential of the nanoclay is at least -5mV, preferably at least -10mV, more preferably at least -15mV, more preferably at least -20mV, and most preferably at least -22mV.
[0052] The zeta potential, particle size distribution and z-average particle size of the nanoclay can be tested by subjecting a 0.1 wt.% aqueous dispersion of the nanoclay to ultrasonic treatment at 25°C for 30 minutes. The zeta potential, particle size distribution and z-average particle size of the nanoclay are measured for the nanoclay in the aqueous dispersion, not the nanoclay in the composition. The zeta potential of the nanoclay can be measured by a Mastersizer S (Malvern Instruments Ltd., UK); the particle size distribution and z-average particle size can be measured by dynamic light scattering, for example, using a Zetasizer Nano ZSE (Malvern Instruments Ltd.); the Z-average particle size refers to the intensity-weighted average hydrodynamic size of a collection of particles measured by dynamic light scattering (for example, using a Zetasizer Nano ZSE (Malvern Instruments Ltd.). The D10, D30, D50, D70 and D90 of the nanoclay can be obtained from the particle size distribution measured as described above.
[0053] The inventors have found that nanoclays with a smaller z-average particle size can improve the dispersibility of alumina particles, extend the shelf life of the composition, reduce the number of pits on the substrate surface, and reduce surface roughness. It was found that nanoclays with a larger z-average particle size can cause the aggregation and agglomeration of alumina abrasive particles, resulting in a greater increase in the D10, D30, D50, D70, and D90 measured by alumina in the composition, and the increase caused by the increase in surface roughness and surface defects (such as pits). And the inventors have found that nanoclays with nanometer size can improve the surface morphology of stainless steel, while nanoclays with micrometer size can deteriorate the apparent morphology of stainless steel. The nanoclay should have a suitable z-average particle size. Preferably, the nanoclay has a z-average particle size of at most 1100nm, preferably at most 1050nm, preferably at most 1000nm, preferably at most 990nm, preferably at most 980nm, and more preferably at most 970nm measured by dynamic light scattering. However, if the z-average particle size of the nanoclay is too small, the viscosity of the composition will be affected, resulting in an adverse effect. Preferably, the nanoclay has a z-average particle size of at least 1 nm, preferably at least 2 nm, preferably at least 5 nm, preferably at least 10 nm, preferably at least 15 nm, more preferably at least 20 nm measured by dynamic light scattering. In a preferred embodiment, the nanoclay preferably has a z-average particle size of 1 nm to 1100 nm, preferably 2 nm to 1050 nm, preferably 5 nm to 1000 nm, preferably 10 nm to 990 nm, preferably 15 nm to 980 nm, more preferably 20 nm to 970 nm measured by dynamic light scattering.
[0054] Experiments have shown that nanoclays with smaller D10 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D10 of at most 600nm, more preferably at most 550nm, more preferably at most 500nm, more preferably at most 450nm, and most preferably at most 400nm as measured by dynamic light scattering. However, if the D10 of the nanoclay is too small, the material removal rate will be reduced. Preferably, the nanoclay has a D10 of at least 0.01nm, more preferably at least 0.05nm, more preferably at least 0.1nm, more preferably at least 0.5nm, and most preferably at least 1nm as measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D10 of 0.01nm to 600nm, 0.05nm to 550nm, 0.1nm to 500nm, more preferably 0.5nm to 450nm, and more preferably 1nm to 400nm as measured by dynamic light scattering.
[0055] Experiments have shown that nanoclays with smaller D30 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D30 of at most 1100nm, more preferably at most 1050nm, more preferably at most 1000nm, more preferably at most 950nm, and most preferably at most 900nm measured by dynamic light scattering. However, a smaller D30 of the nanoclay will reduce the material removal rate. Preferably, the nanoclay has a D30 of at least 0.05nm, more preferably at least 0.1nm, more preferably at least 0.5nm, more preferably at least 1nm, and most preferably at least 1.3nm measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D30 of 0.05nm to 1100nm, more preferably 0.1nm to 1050nm, more preferably 0.5nm to 1000nm, more preferably 1nm to 950nm, and most preferably 1.3nm to 900nm measured by dynamic light scattering.
[0056] Experiments have shown that nanoclays with smaller D50 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D50 of at most 1300nm, more preferably at most 1200nm, more preferably at most 1100nm, more preferably at most 1000nm, more preferably at most 950nm measured by dynamic light scattering. However, a smaller D50 of the nanoclay will reduce the material removal rate. Preferably, the nanoclay has a D50 of at least 0.1nm, more preferably at least 0.5nm, more preferably at least 1nm, more preferably at least 1.3nm, and most preferably at least 1.5nm measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D50 of 0.1nm to 1300nm, more preferably 0.5nm to 1200nm, more preferably 1nm to 1100nm, more preferably 1.3nm to 1000nm, and most preferably 1.5nm to 950nm as measured by dynamic light scattering.
[0057] Experiments have shown that nanoclays with smaller D70 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D70 of at most 1600nm, more preferably at most 1550nm, more preferably at most 1500nm, more preferably at most 1450nm, and most preferably at most 1400nm measured by dynamic light scattering. However, a smaller D70 of the nanoclay will reduce the material removal rate. Preferably, the nanoclay has a D70 of at least 0.5nm, more preferably at least 1nm, more preferably at least 1.4nm, more preferably at least 1.8nm, and most preferably at least 2nm measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D70 of 0.5nm to 1600nm, more preferably 1nm to 1550nm, more preferably 1.4nm to 1500nm, more preferably 1.8nm to 1450nm, and most preferably 2nm to 1400nm measured by dynamic light scattering.
[0058] Experiments have shown that nanoclays with smaller D90 can achieve smaller surface roughness during CMP treatment. Preferably, the nanoclay has a D90 of at most 2000nm, more preferably at most 1950nm, more preferably at most 1900nm, more preferably at most 1800nm, and most preferably at most 1700nm measured by dynamic light scattering. However, a smaller D90 of the nanoclay will reduce the material removal rate. Preferably, the nanoclay has a D90 of at least 1nm, more preferably at least 2nm, more preferably at least 3nm, more preferably at least 3.5nm, and most preferably at least 4nm measured by dynamic light scattering. In a preferred embodiment, the nanoclay has a D90 of 1nm to 2000nm, more preferably 2nm to 1950nm, more preferably 3nm to 1900nm, more preferably 3.5nm to 1800nm, and most preferably 4nm to 1700nm measured by dynamic light scattering.
[0059] The increase of the aluminum oxide particles D10, D30, D50, D70, and D90 refers to the ratio of the particle size of the aluminum oxide particles in the composition to the particle size of the aluminum oxide particles in the aqueous dispersion (regardless of the composition containing what ingredients), which is specifically obtained by laser diffraction measurement, and specifically refers to: the corresponding ratio of the particle size of the aluminum oxide particles measured in the composition to the particle size of the aluminum oxide particles measured in the aluminum oxide dispersion (85wt.% water) with an aluminum oxide concentration of 15wt.%. The inventors have found that the nanoclay of the present invention can reduce the increase ratio of the aluminum oxide particles D10, D30, D50, D70, and D90. Preferably, the increase ratio of the aluminum oxide D10 in the composition containing nanoclay to the aluminum oxide D10 measured in the aluminum oxide dispersion (85wt.% water) with an aluminum oxide concentration of 15wt.% is at most 3.5, more preferably at most 3, more preferably at most 2.5, and most preferably at most 2. Preferably, the ratio of the increase of D30 of alumina in the composition to the D30 of alumina measured in a dispersion of alumina having an alumina concentration of 15 wt.% (85 wt.% water) is at most 4.2, preferably at most 3.5, more preferably at most 3, more preferably at most 2.5. Preferably, the ratio of the increase of D50 of alumina in the composition to the D50 of alumina measured in a dispersion of alumina having an alumina concentration of 15 wt.% (85 wt.% water) is at most 5.5, preferably at most 5, further preferably at most 4.5, and even more preferably at most 4. Preferably, the ratio of the increase of D70 of alumina in the composition to the D70 of alumina measured in a dispersion of alumina having an alumina concentration of 15 wt.% (85 wt.% water) is at most 5.5, preferably at most 5, further preferably at most 4.5, and even more preferably at most 4. Preferably, the increased ratio of D90 of alumina in the composition to D90 of alumina measured in a dispersion of alumina having an alumina concentration of 15 wt.% (85 wt.% water) is at most 5.5, preferably at most 5, further preferably at most 4.5, and most preferably at most 4.
[0060] The composition also optionally comprises one or more preservatives. The preservative can be any suitable compound that prevents, inhibits, reduces growth, inhibits activity or eliminates unwanted microorganisms. Examples of suitable preservatives include sodium hypochlorite, methylisothiazolinone, benzisothiazolinone, chloromethylisothiazolinone and combinations thereof. Preferably, the composition comprises at least 0.6ppm by weight, more preferably at least 1.6ppm by weight, more preferably at least 2.7ppm by weight, more preferably at least 3.8 by weight, most preferably at least 4.6ppm by weight of preservative. High concentrations of preservatives can cause undesirable interactions between preservatives and other components of the composition and substrates. Therefore, the composition preferably comprises at most 98ppm by weight, more preferably at most 83ppm by weight, more preferably at most 74ppm by weight, most preferably at most 69ppm by weight of preservative. Ppm used herein refers to ppm by weight.
[0061] Preferably, the composition is substantially free of polymers. The polymer may be any polymer. Typically, polymers are used in CMP compositions containing aluminum oxide to improve the dispersibility of the aluminum oxide particles, thereby increasing the shelf life of the composition and preventing particle aggregation that may cause surface defects of the substrate. However, during CMP polishing, polymers typically reduce the material removal rate of the substrate. Surprisingly, it was found that even in the absence of a polymer, the composition according to the present invention caused fewer defects in the substrate surface.
[0062] As used herein, the term "substantially free of component X" refers to a composition that does not substantially contain the component X, ie, such component may at most be present in the composition as an impurity or contaminant but is not added to the composition as a separate component.
[0063] The present invention also provides a method for chemical mechanical polishing of a substrate, the method comprising the following steps: (a) providing a chemical mechanical polishing composition; (b) contacting the substrate with the chemical mechanical polishing composition and a polishing pad; (b) moving the polishing pad relative to the substrate with the composition located therebetween; (c) removing at least a portion of the substrate. The CMP composition provided in step (a) is a composition of the present invention. The method may optionally include other steps.
[0064] The composition can be prepared using suitable techniques known to those skilled in the art. The abrasive particles, nanoclays and other chemical additives as described above can be added to the aqueous carrier in any order and in suitable amounts to achieve the desired concentration. The abrasive particles, nanoclays and other chemical additives can be mixed and stirred in the aqueous carrier. The pH value can be adjusted using the above-mentioned pH regulators and pH buffers to obtain and maintain the desired pH. The abrasive particles, nanoclays and other chemical additives can be added at any time before use (e.g., one month, one day, one hour or one minute) or during the CMP process.
[0065] The composition can be provided as a one-part system, a two-part system, or a multi-part system. For example, as a two-part system, the first part can include abrasive particles and one or more chemical additives, and the second part can include nanoclay and one or more other chemical additives. The first part and the second part can be mixed at any time before the CMP treatment (e.g., one month, one day, one hour, or one minute) or during the CMP treatment, such as when using a polishing device with multiple supply paths for the CMP composition.
[0066] The composition may be provided as a concentrate and may be diluted with an appropriate amount of water prior to use. The concentration of the components in the composition may be any suitable, for example 2, 3, 10 or 25 times the above-mentioned concentrations for use. For example, the concentrate may contain abrasive particles and chemical additives in concentrations such that after dilution with an appropriate amount of water, the abrasive particles and chemical additives are present in the composition at the above-mentioned concentrations. If the composition is provided, for example, as a two-part system, one or both parts may be provided as a concentrate. The two parts may be provided at different concentrations, for example the first part may be three times concentrated and the second part may be five times concentrated. The two parts may be diluted in any order prior to mixing.
[0067] The composition should achieve high material removal rates for substrates containing ferrous metal alloys, such as stainless steel, carbon steel, leaded steel, tool steel and cast steel during CMP processing. Preferably, the composition exhibits a material removal rate for substrates containing ferrous metal alloys of at least 8 μm / h, more preferably at least 13 μm / h, more preferably at least 21 μm / h, more preferably at least 25 μm / h during CMP processing.
[0068] The present invention also relates to the use of the composition of the present invention. The composition of the present invention can be used to polish various materials. Preferably, the composition of the present invention is used for chemical mechanical polishing of a substrate comprising one or more materials, the material comprising a metal, a semi-metal, a metal alloy, a metal oxide, a semi-metal oxide, a carbide, a mineral, a plastic or a combination thereof. As known to those skilled in the art, chemical mechanical polishing refers to the process of placing a substrate in a CMP apparatus so that it contacts a polishing pad and a CMP composition located therebetween. The polishing pad moves relative to the substrate to remove a portion of the substrate.
[0069] For some materials such as metals, metal alloys, metal oxides and minerals, the compositions are used in a final polishing step, while for other materials such as ceramics and plastics, the compositions are used in intermediate polishing steps.
[0070] Examples of metals, metal alloys and metal oxides that can be polished with the composition of the present invention are iron, iron alloys (e.g., steel), aluminum, aluminum alloys, titanium, titanium alloys, nickel, nickel alloys, copper, copper alloys, Kovar, white copper, Inconel, brass, niobium, bronze, nickel silver, beryllium, monel, vanadium, Hastelloy, tantalum, silver, gold, molybdenum, Nimonic alloys, Waspaloy alloys, tungsten, ceramics, and combinations thereof. The metal oxides can be in the form of single crystals, polycrystalline, sintered bodies (ceramics), or combinations thereof.
[0071] In a particularly preferred embodiment, the present invention is used for chemical mechanical polishing of a substrate comprising a metal alloy. The metal alloy may comprise a metal as its main component and at least one metal different from the main component. The number of metal species different from the main component is not limited, for example, it may be two, three or more. The metal preferably used as the main component of the metal alloy is selected from aluminum, titanium, magnesium, iron, nickel and copper. In a particularly preferred embodiment, the main metal species is iron. Examples of ferroalloys include stainless steel, carbon steel, alloy steel, leaded steel, tool steel, cast steel, maraging steel, cast iron and combinations thereof.
[0072] The present application is described in detail below through specific embodiments.
[0073] Example 1
[0074] The stainless steel material removal rate, surface roughness and surface defects of the polished products of composition A1 and compositions E1-E7 were evaluated. Composition A1 and compositions E1-E7 all contained 15 wt.% of aluminum oxide abrasive particles, 1 wt.% of hydrogen peroxide, 1 wt.% of laponite having a z-average particle size of 61.75 nm and a zeta potential of -31 mV, and 30 ppm (by weight) of the preservative KATHON TMLX 150 (Dow Inc.). The pH of these compositions was adjusted to 6.5 using KOH. All compositions were free of polymer. Compositions E1-E7 also contained 2 wt.% of a complexing agent, the specific ingredients of which are shown in Table 1.
[0075] The z-average particle size of the aluminum magnesium silicate was measured by dynamic light scattering using a Zetasizer Nano ZSE (Malvern Instruments Ltd., UK) from a 0.1 wt% dispersion and the D50 was obtained as described above. The zeta potential of the nanoclay was measured in a 0.1 wt% aqueous dispersion using a Mastersizer S (Malvern Instruments Ltd., UK). Prior to measuring the z-average particle and zeta potential, the aluminum magnesium silicate aqueous dispersion was sonicated for 30 minutes at 25°C to obtain a uniform dispersion.
[0076] As described above, before the aluminum oxide abrasive particles are added to the composition, the D30, D50, D70 and D90 of the aluminum oxide abrasive particles are obtained by laser diffraction in an 85 wt.% aqueous solution using Horiba LA960. After the aluminum oxide particles are dispersed, the D30, D50, D70 and D90 of the aluminum oxide abrasive particles are measured in the composition using Horiba LA960. As described above, the increase ratio of D30, D50, D70 and D90 is obtained by calculating the ratio of the corresponding particle size of the aluminum oxide abrasive particles dispersed in the composition to the corresponding particle size of the aluminum oxide abrasive particles dispersed in the 85 wt.% aqueous solution.
[0077] A Nano-Max polishing tool (Shenzhen Nanos Precision Machinery Technology Co., Ltd.) was used to polish the surface of the 9 cm2 surface at a platen speed of 80 rpm, a down force of 2.0 psi, and a slurry flow rate of 100 ml / min. 2 , a stainless steel plate with a thickness of 3 mm was polished for 4 minutes.
[0078] The polished stainless steel plates were visually inspected for surface defects, and the pits were counted and classified as A = no corresponding defects, B = less than 10 corresponding defects, and C = more than 10 corresponding defects, and the results are shown in Table 1. The material removal rate of the stainless steel plate was measured using an electronic balance, and the weight difference before and after polishing was calculated. The material removal rate is listed in Table 1 as a percentage of the material removal rate of composition A1. The surface roughness (average roughness, Ra) was measured using an SJ-410 surface roughness tester (Mitutoyo Corp) at a measuring length of 25 mm and is listed in Table 1. As known to those skilled in the art, surface roughness is the arithmetic mean of the absolute value of the deviation of the profile height from the average height within the measuring length. In addition, all surface roughness values below 0.02 can be considered good.
[0079] Table 1
[0080]
[0081] As can be seen from Table 1, compositions E1-E7 containing different complexing agents have higher removal rates than A1 without complexing agent. In addition, E5 using only HEDP as complexing agent has no pits and has the lowest surface roughness. Compositions E1-E4 and E6-E7 using other complexing agents have unsatisfactory effects.
[0082] Example 2
[0083] Composition A2 and compositions E8-E11 were evaluated for stainless steel material removal rate, surface roughness, and surface defects. Composition A2 and compositions E8-E11 included 15 wt.% aluminum oxide abrasive particles, 2 wt.% 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP), 1 wt.% bentonite having a z-average particle size of 444.5 nm and a zeta potential of -28.9 mV, and 30 ppm (by weight) of the corrosion inhibitor KATHON TM LX 150 (Dow Inc.). The pH of these compositions was adjusted to 6.5 using KOH. Compositions E8-E11 also contained 1 wt.% of an oxidizing agent as shown in Table 2.
[0084] Before polishing, the zeta potential of the aluminum oxide particles in the composition was measured using a Mastersizer S (Malvern Instruments Ltd., UK). The stainless steel plate was polished and its relative removal rate, surface roughness and pits were measured as described in Example 1. The results are shown in Table 2.
[0085] Table 2
[0086]
[0087] As can be seen from Table 2, the composition using only hydrogen peroxide and nitrous acid showed no defects, and the composition E8 using hydrogen peroxide showed the lowest surface roughness.
[0088] Example 3
[0089] Compositions A3-A4 and E12 were evaluated for stainless steel material removal rate, surface roughness, and surface defects. Compositions A3-A4 and E12 included 15 wt.% aluminum oxide abrasive particles, 1 wt.% hydrogen peroxide, 2 wt.% 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP), 1 wt.% magnesium aluminum silicate having a z-average particle size of 91.11 nm and a zeta potential of -29.8 mV, and 30 ppm (by weight) of a corrosion inhibitor KATHON TM LX 150 (Dow Inc.). These compositions were adjusted to have different pH values using KOH, as shown in Table 3.
[0090] The stainless steel plate was polished and its relative removal rate, surface roughness and pits were measured as described in Example 1. The results are shown in Table 3.
[0091] The static corrosion of each composition on stainless steel was evaluated by measuring the weight of the stainless steel plate. The weight of the stainless steel was measured first, then the stainless steel plate was placed in the composition, heated to 60°C, and left to stand for 5 hours, after which the weight of the stainless steel plate was measured again. The difference in weight before and after (weight loss due to corrosion) is the static corrosion.
[0092] Table 3
[0093] A3 E12 A4 pH 3.5 6.5 9.5 Relative removal rate [%] 100% 83% 33% 60℃ static corrosion (g / h) 0.03 0.01 0.0058 Roughness Ra(um) 0.02 0.018 0.025 Pitfalls A A C
[0094] As can be seen from Table 3, the composition with an alkaline pH exhibits the lowest static corrosion, indicating less corrosion, but the relative removal rate is not high, and there are many defects in the polished stainless steel plate; the relative removal rate of the composition E12 with a neutral pH is slightly lower than that of the acidic composition, but its static corrosion is lower than that of the acidic composition, its roughness is lower than that of the acidic composition, and there are no defects like the acidic composition, so it is acceptable.
[0095] Example 4
[0096] Compositions A5-A9 and E13-E18 were evaluated for stainless steel material removal rate, surface roughness, and surface defects. Compositions A5-A9 and E13-E18 included 15 wt.% aluminum oxide abrasive particles, 1 wt.% hydrogen peroxide, 2 wt.% 1-hydroxyethylidene-1,1-diphosphonic acid (HEDP), and 30 ppm (by weight) of the corrosion inhibitor KATHONTM LX 150 (Dow Inc.). The pH of these compositions was 6.5. Except for A5, all other compositions also contained 1 wt.% of nanoclays as shown in Table 4. Zeta potential and z-average particle size of the nanoclays listed in Table 4 were measured using a Zetasizer Nano ZSE (Malvern Instruments Ltd., UK) as described in Example 1 before adding the nanoclays to the compositions.
[0097] The stainless steel plates were polished and the relative removal rate, surface roughness and pits were measured as described in Experiment 1, and the results are shown in Table 4.
[0098] The shelf life of compositions A5-A9 and compositions E13-E18 was evaluated by placing 500 mL of each composition into a 500 mL polyethylene bottle and leaving it at room temperature without stirring. The "shelf life" is defined as the time from when the composition begins to stand until the composition settles and forms a hard cake that is not easily redispersed. The results of the shelf life evaluation are shown in Table 4.
[0099] Table 4
[0100]
[0101] From Table 4 we can see that:
[0102] Although the relative removal rates of compositions E13 and E14 containing magnesium aluminum silicate with nanoclay z-average particle size less than 1000 nm are not the highest, they show lower surface roughness and no pits, among which composition E13 containing magnesium aluminum silicate with nanoclay z-average particle size less than 100 nm shows higher relative removal rate, good surface roughness and no pits; compositions E15-18 containing bentonite and laponite with nanoclay z-average particle size less than 1000 nm show lower surface roughness and no pits, among which composition E17 containing bentonite and laponite with nanoclay z-average particle size less than 100 nm shows good surface roughness and no pits.
[0103] The shelf life is obtained by observing the composition at room temperature. For composition A5 without nanoclay, the aluminum oxide settled after 5 days and formed a hard cake that was not easily redispersed. All compositions A6-A9 and compositions E13-E18 containing nanoclay were observed for up to 9 months and found to be still dispersed (not settled) after 9 months. After 9 months, no further observation was made on the composition.
[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A chemical mechanical polishing composition for a metal alloy surface, comprising aluminum oxide abrasive particles, an oxidizing agent, a dispersant and a pH regulator, wherein: The dispersant is a nanoclay having a z-average particle size of at most 1000 nm.
2. The composition according to claim 1, characterized in that The nanoclay has a zeta potential of at least -5 mV.
3. The composition according to claim 1, characterized in that The aluminum oxide abrasive particles have a negative zeta potential in the composition at a pH of at least 5.
0.
4. The composition according to claim 1, characterized in that The oxidant is an inorganic peroxide compound, an organic peroxide compound, or a combination thereof.
5. The composition according to claim 1, characterized in that The composition further comprises a complexing agent, which is a dicarboxylic acid, a polycarboxylic acid, an amino acid, an organic amine, an aminocarboxylic acid, a polyaminopolycarboxylic acid, a phosphate, a polyphosphate, an organic phosphonic acid, a phosphonocarboxylic acid, a phenol derivative, a ketone, or a combination thereof.
6. The composition according to claim 5, characterized in that The complexing agent is an organic phosphonic acid.
7. The composition according to any one of claims 5 to 6, characterized in that The composition comprises 0.1 wt% to 33.3 wt% of a complexing agent.
8. The composition according to claim 1, characterized in that The composition comprises 0.0001 wt % to 15 wt % of nanoclay.
9. The composition according to claim 1, characterized in that The pH adjuster is an alkali metal hydroxide, a quaternary ammonium hydroxide, an alkali metal carbonate, or a combination thereof.
10. A polishing method for a metal alloy substrate, the method being achieved by using the composition according to any one of claims 1 to 9.
Citation Information
Patent Citations
Polishing liquid for stainless steel part of mobile phone and preparation method thereof
CN108441122A
Chemical mechanical polishing composition with improved recycling performance
CN115926629A
Chemical mechanical polishing composition with improved particles
CN115960540A
Chemical mechanical polishing composition for metal alloy CMP
CN116000782A
Method chemical-mechanical polishing and planarizing corundum, GaAs, GaP and GaAs / GaP alloy surfaces
US20050233680A1